Metronidazole associated seizures: a case report and review of the pharmacovigilance literature - Ogundipe, Olayinka A. (International Journal of Basic & Clinical Pharmacology, 2017)
Seizures are a rare side-effect associated with the use of metronidazole. This report describes the case of an 83-year old patient with previous cerebral injury in whom new onset seizures were triggered soon after the commencement of treatment with metronidazole at conventional adult doses for Clostridium difficile-associated diarrhoea. A brief review of the medical pharmacovigilance literature in relation to metronidazole and seizures is presented. Two causality assessment systems are applied to the index case report, to illustrate their potential use in supporting increased objectivity when reporting suspected ADRs in clinical practice.